Revision and update of the consensus definitions of invasive fungal disease from the European Organization for Research and Treatment of Cancer and the Mycoses Study Group Education and Research Consortium - Donnelly, J Peter; Chen, Sharon C.; Kauffman, Carol A.; Steinbach, William J.; Baddley, John W.; Verweij, Paul E.; Clancy, Cornelius J.; Wingard, John R.; Lockhart, Shawn R.; Groll, Andreas H.; Sorrell, Tania C.; Bassetti, Matteo; et al. (Clinical infectious diseases, 2020)
European Organization for Research and Treatment of Cancer and the Mycoses Study Group definitions for probable invasive fungal disease now include solid organ